Impacts of two types of El Niño events on spring surface air temperature over Sri Lanka - Kajakokulan, Pathmarasa; Attada, Raju; Nguyen-Le, Dzung; Chowdary, Jasti S. (Dynamics of atmospheres and oceans, 2025)
The relationship between El Niño events and surface air temperature (SAT) over Sri Lanka (SL) has been well documented. However, the impact of the two different types of El Niño flavors on seasonal SAT variability in SL remains to be thoroughly investigated. Therefore, to identify the effect of two different types of El Niño on SAT over SL, we analyzed reanalysis and observational datasets from 1981 to 2020. This study mainly focused on the boreal spring season during the decaying phase of El Niño events. We show the presence of a strong SAT cooling in spring over the SL during the decaying phase of Central Pacific (CP) El Niño events, while intense spring SAT warming over SL is particularly pronounced during the Eastern Pacific (EP) El Niño decaying phase. It is found that low-level convergence over SL and the east coast of India associated with easterlies extending from the southern flank of the westward-shifted Western North Pacific anticyclones (WNPA) lead to updrafts. This results in enhanced cloud conditions and decreased incoming shortwave radiation, thereby causing strong cooling during CP El Niño events. Conversely, during EP El Niño, the WNPA shifts eastward, and the easterlies are confined around the equator, which helps develop the anti-cyclonic circulation over the Bay of Bengal (BoB). As a result, anomalous low-level divergence induces a strong downdraft over SL. This leads to cloud-free conditions and significantly enhanced incoming shortwave radiation during EP El Niño events, helping to enhance the SAT warming over SL. In addition, a composite analysis of CP and EP El Niño events demonstrated that strong cool (warm) conditions are prevalent in CP (EP) El Niño decaying spring years. This study highlights two distinct types of El Niño as a significant driver for understanding the SAT variability in Sri Lanka. •A strong SAT cooling in spring over the SL during the decaying phase of Central Pacific (CP) El Niño events, while intense spring SAT warming over SL during the Eastern Pacific (EP) El Niño decaying phase.•The low-level convergence over SL from easterlies from Western North Pacific anticyclones (WNPA) leads to updrafts, enhanced cloud conditions, and decreased incoming shortwave radiation, causing strong cooling during CP El Niño.•Low-level divergence over SL, and strong anticyclonic circulation over the Bay of Bengal, induces downdrafts, cloud-free conditions, and enhanced shortwave radiation, leading to SAT warming during EP El Niño.